1993
DOI: 10.1111/j.1365-2672.1993.tb02768.x
|View full text |Cite
|
Sign up to set email alerts
|

Survival of pathogenic bacteria during mesophilic anaerobic digestion of animal waste

Abstract: The survival of pathogenic bacteria was investigated during the operation of a full-scale anaerobic digester which was fed daily and operated at 28 degrees C. The digester had a mean hydraulic retention time of 24 d. The viable numbers of Escherichia coli, Salmonella typhimurium, Yersinia enterocolitica, Listeria monocytogenes and Campylobacter jejuni were reduced during mesophilic anaerobic digestion. Escherichia coli had the smallest mean viable numbers at each stage of the digestion process. Its mean T90 va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0
2

Year Published

1997
1997
2021
2021

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 84 publications
(51 citation statements)
references
References 8 publications
4
45
0
2
Order By: Relevance
“…Nevertheless, we did isolate 95 Campylobacter isolates from compost, including at later stages of the composting process (i.e., days 15 to 126). Using culture-based enumeration methods, previous studies concluded that campylobacters (primarily C. jejuni bacteria) do not persist well in solid manure (7,11,12,26,32,39) or in thermophilic anaerobic manure digesters (35,36) but can survive for prolonged periods in mesophilic anaerobic digesters (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, we did isolate 95 Campylobacter isolates from compost, including at later stages of the composting process (i.e., days 15 to 126). Using culture-based enumeration methods, previous studies concluded that campylobacters (primarily C. jejuni bacteria) do not persist well in solid manure (7,11,12,26,32,39) or in thermophilic anaerobic manure digesters (35,36) but can survive for prolonged periods in mesophilic anaerobic digesters (18,19).…”
Section: Discussionmentioning
confidence: 99%
“…Used litter from broiler houses presumably contains large numbers of campylobacteria when removed from the house. Experiments have shown that C. jejuni has a good ability to survive during anaerobic digestion of animal waste (10,11). An earlier study showed that houseflies can function as a vector for C. jejuni when a reservoir is located near the broiler house (20).…”
Section: Discussionmentioning
confidence: 99%
“…Kearney et al (50) utilized mesophilic anaerobic digestion to analyze the survival of pathogenic bacteria in animal waste. The group found that viable numbers of E. coli, S. enterica serovar Typhimurium, Yersinia enterocolitica, Listeria monocytogenes, and Campylobacter jejuni were reduced during processing and that indigenous bacterial strains survived better than laboratory strains, consistent with previous results (65,69).…”
Section: Anaerobic and Aerobic Digestionmentioning
confidence: 99%